MODELO DE INTERVENCION PARA LA GOBERNABILIDAD Y EL DESARROLLO URBANO PARTICIPATIVO. EL RESCATE DE RIBERAS DEL BRAVO, CIUDAD JUAREZ, CHIHUAHUA, MEXICO - Peña, Leticia (European Scientific Journal, ESJ, 2013)
Ciudad Juarez, Chihuahua, Mexico presents conditions of social instability with violent incidents linked to organized crime since 2008. The sale of drugs at retail in the suburbs, is transformed and has effects on the daily lives of the inhabitants of the new subdivisions. This actual job of applied research, aims to present part of the diagnosis and development of agreements that brings participatory methodology of the Neighborhood Strategic Plan (ENP) developed in 2011, linking the empowerment of various actors and natural or elected leaders, modifying the deteriorated conditions of the sector through successful management of support and equipment, which has had a fast and effective impact to enroll in the proposed development of the municipal government, to define mechanisms for citizens to be responsible with government action, which strengthens governance and social improvement. The applied methodology is based on perceptual proactive diagnostics, development of popular consultation workshops, emblematic action of participants, the delivery of the Neighborhood Strategic Plan to the Mayor and community work-shop followed for one year.